PROSES PEMERIKSAAN PERKARA DI MUKA PERSIDANGAN PADA DAKWAAN TINDAK PIDANA DAN BENDA SITAAN DALAM PROSES PERADILAN - Djufri, Darmadi (Solusi, 2022)
The process of examining cases before a trial against someone being charged for committing a crime is that at first a judge conducts an examination and reads out the case in court regarding the defendant's problem. If the judge considers that the examination of the court hearing has been completed, the judge invites the public prosecutor to read out his demands. Such provisions can be found in the Criminal Procedure Code, namely in Article 182 paragraph (l) which reads as follows: a. After the examination is declared complete, the public prosecutor submits a criminal charge; b. Furthermore, the defendant and/or his legal advisor may present his/her defense which can be answered by the public prosecutor, provided that the defendant or legal advisor always gets the last turn, c. Claims, pleas, and answers to defenses are made immediately. In the Code of Criminal Procedure it is clearly stated that those subject to confiscation are: a. The object or claim of the suspect or defendant is wholly or partly suspected to have been obtained from a criminal act or part of the proceeds of a criminal act; b. Objects that are used directly to commit a crime or to prepare, for example a knife or what weapon is used to kill; c. Items needed to hinder the investigation of a criminal act; d. Objects specially made or intended to commit a crime; e. Other objects that have a direct relationship with the crime committed; f. Items that are confiscated due to civil cases or bankruptcy can also be confiscated for the purposes of investigation, prosecution and trial of criminal cases as long as it concerns the provisions of paragraph (1) Article 39 of the Criminal Procedure Code.